The Kenyan runners - Larsen, H. B.; Sheel, A. W. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Today the Kenyan dominance in middle- and long-distance running is so profound that it has no equivalence to any other sport in the world. Critical physiological factors for performance in running include maximal oxygen consumption (VO2max), fractional VO2max utilization and running economy (energetic cost of running). Kenyan and non-Kenyan elite runners seem to be able to reach very high, but similar maximal oxygen uptake levels just as there is some indication that untrained Kenyans and non-Kenyans have a similar VO2max. In addition, the fractional utilization of VO2max seems to be very high but similar in Kenyan and European runners. Similarly, no differences in the proportion of slow muscle fibers have been observed when comparing Kenyan elite runners with their Caucasian counterparts. In contrast, the oxygen cost of running at a given running velocity has been found to be lower in Kenyan elite runners relative to other elite runners and there is some indication that this is due to differences in body dimensions. Pulmonary system limitations have been observed in Kenyan runners in the form of exercise-induced arterial hypoxemia, expiratory flow limitation, and high levels of respiratory muscle work. It appears that Kenyan runners do not possess a pulmonary system that confers a physiological advantage. Additional studies on truly elite Kenyan runners are necessary to understand the underlying physiology which permits extraordinary running performances.